PENGAWASAN LIMBAH BAHAN BERBAHAYA DAN BERACUN PT. MAKASSAR TENE PADA DINAS PENGELOLAAN LINGKUNGAN HIDUP SULAWESI SELATAN - Permatasari, Sriwahyuni; Parawu, Hafiz Elfiansyah; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out the supervision of B3 waste PT. Makassar Tene at the South Sulawesi Environmental Management Service. This study used a qualitative research method with a descriptive type of research. The results of this study showed 3 (three) monitoring techniques carried out by the South Sulawesi DPLH in supervising the management of B3 waste at PT. Makassar Tene, namely: 1) Monitoring, that direct monitoring had not carried out direct monitoring due to the Covid 19 pandemic. Meanwhile, indirect monitoring was carried out through the SIMPEL application; 2) Inspection, that the site inspection and B3 waste management activities had managed properly by submitting B3 waste to a licensed third party. While a comprehensive examination, PT. Makassar Tene so far had complied with all the provisions that had been set; 3) assessment of the implementation of B3 waste management, all B3 waste management processes of PT. Makassar Tene run in accordance South Sulawesi DPLH. Meanwhile, the evaluation of the report on the results of the B3 waste supervision of PT. Makassar Tene by providing PT. Makassar Tene had a blue rating which meant